The Winter Fool: Reflections on Daniel Kehlmann’s Tyll (2017/2020) - Gilloch, Graeme (Simmel Studies, 2025)
This paper uses a constellation of motifs and figures from the writings of Georg Simmel and Walter Benjamin to unfold the legendary character of Tyll Eulenspiegel as portrayed in Daniel Kehlmann’s Booker Prize-shortlisted novel, Tyll (2017; English translation 2020). A motley of trickster, acrobat, hoaxer and clown, Tyll is transplanted by Kehlmann from the fourteenth century into the midst of the Thirty Years War (1618-48) and plies his itinerant trade across the devastated territories of central Europe in a series of episodic and picaresque exploits and encounters. As a wandering will-’o’-the-wisp, the ‘daemonic character’ of Tyll is suggestive of a number of Simmelian social types and Benjaminian dramatis personae: the stranger, the adventurer, the ‘destructive character’ and, above all, the courtly intriguer. I suggest how Tyll intriguingly embodies various attributes and qualities of these figures and, at the same time, playfully eludes and elucidates such constructions and characterizations.